Utilization of Zakat, Infaq, Alms, Waqf (ZISWAF) and the Blessed Friday Phenomenon - Mar'atush Shalihah, Bunga; Hidayat, Fajri Nur; Amelia, Riski (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2023)
In Islam, Friday is a very special day. In Muslim belief, Friday is considered a blessed and sacred day. In addition, understanding the importance of sharing sustenance is also an important part of the teachings of Islam. One of the forms of sharing sustenance recommended in Islam is by carrying out ZISWAF (Zakat, Infaq, Shadaqah, Waqf). The utilization of Ziswaf (Zakat, Infaq, Shadaqah, and Waqf) is one of the efforts made by Muslims in realizing social justice and the economic empowerment of the people. On the other hand, the Friday Blessing phenomenon is a popular tradition among Muslims, where people compete to give alms on Friday in the hope of getting multiple blessings. In this article, the author will discuss the link between the Blessed Friday phenomenon and Ziswaf utilization. The author will explain why Blessed Friday is the right moment for Ziswaf utilization, as well as the benefits of both.